Experiência e mudança: exercícios para fazer sociologia de outra maneira - Santos, Liza Franco Busse Reis dos (2022)
This research is driven by the question "How to do sociology in a different way?" and inspired by the inseparability between research and life. This inseparability is affirmed by experience with which the researcher becomes a craftsman of himself and the research a handmade and procedural construction, as conceiveid by the methodology of Intellectual Craftsmanship formulated by Charles Wright Mills. The affirmation of life in research calls for an ethical look at sociological work and, in these terms, the essay, this language of experience that invites to a self-drive, as treated by the philosopher of education Jorge Larrosa, is present in these pages, as well as the ethics of self-care, studied by Michel Foucault. The thesis is composed of essayistic exercises in which these components are mobilized, and, in these terms, they are attempts at change, experimentations, that problematize the method in the condition of a controlled way for research and producer of the researcher's movement. There is something of freedom in thinking outside the given way, and, in this sense, this research visits Friedrich Nietzsche's Extemporaneous Considerations and places the themes of craftsmanship and the essay in relation to the becoming, treated by Gilles Deleuze. The essay is, here, a platform for the researcher's subjectivation and a shadow of disciplinary sociology cast over the writing in which the researcher was forged, notably in the process of formal education for sociological research. To go to the shadows is to escape the conventional way of research and for this the thesis calls upon the sociologist Gabriel Tarde, a contemporary of Émile Durkheim and an opponent of his sociology, and reflections on the essay. The alliance with shadows matters insofar as what is at issue is to change, to move out of what is going on, out of this which is given (and assured) to the researcher and to the research. This movement of change involves, above all, attention to experience, always singular, and to affirm it is also to multiply ways of thinking and doing research.